Assessing long term impact of regional climate and human activities on vegetation greenness dynamics in Sundarbans - Muhammad Sadiq Khan; Ayesha Akter; Ismail Khan; Luis Carlos Ramos Aguila; Lina Akter; Mengmeng Yang; Xu Li; Yuelin Li (Ecological Informatics)
Global climate change and human activities significantly influence mangrove greenness dynamics. Assessing the greenness trends in key regions of the Sundarbans in relation to regional climate factors and understanding the impacts of human activities on the mangrove landscape over recent decades are critical for effective ecosystem management such as landscape and land-use planning, which could eventually preserve the functionality of this ecosystems. The Sundarbans, located in the delta region spanning coastal areas of southern Bangladesh and eastern India, serves as a key study area. We used long-term MODIS-NDVI data (2000−2020) alongside major climatic factors to analyze greenness trends, while also utilizing Landsat data (1989–2020) to assess human-induced disturbances in the Sundarbans landscape through standard land cover monitoring techniques. The results revealed a significant annual increase in greenness (0.0021/year, p = 0.01), with a more pronounced improvement in the wet season (0.0026/year, p = 0.001) compared to the dry season (0.0016/year, p = 0.05). Climatic factors, including annual mean precipitation and air temperature, were strongly correlated with greenness, influencing 76 % and 78 % of the pixels, respectively, with increased rainfall observed in dense mangrove areas. During the wet season, greenness expanded, showing significant correlations with precipitation (78 %) and air temperature (81 %) across most regions, except in the central Sundarbans. In contrast, dry season precipitation was negatively correlated with 51 % of greenness pixels, and canopy surface temperature showed a negative correlation with both annual and seasonal greenness, particularly during the dry season (61 % of pixels). Overall, greenness increased annually in 92 % of pixels, with a 94 % increase in the wet season and an 89 % increase in the dry season. However, human-induced aquaculture activities expanded by 5.8 % in the Sundarbans, posing potential risks to the stability of the mangrove ecosystem. These findings highlight the critical role of regional precipitation and air temperature in enhancing mangrove greenness, despite some negative human influences. The results emphasize the need for sustainable land-use policies and conservation efforts to safeguard mangrove ecosystems. The outcomes also provide valuable insights for future sustainability strategies aimed at enhancing greenness resilience in the central and southeast regions of the Sundarbans, ensuring the long-term preservation of the natural mangrove landscape.